The Effectiveness of a Strategy Based on Teaching Thinking in Developing the Critical Reading Skills of Fifth-Grade Students - Al-Hawamdeh, Mohammad (Jordan Journal of Educational Sciences, 2015)
This study aimed at examining the effectiveness of the TIPS strategy for teaching thinking in developing the critical reading skills of fifth-grade students in the Governorate of Irbid. The sample of this study consisted of 109 male and female students from two separate schools (one school for boys and one school for girls). The experimental group included 28 male and 26 female students, who were taught to follow the TIPS strategy. On the other hand, the control group included 28 male and 27 female students, who were taught by means of the traditional approach. The results showed that there was a statistically significant difference in the level of performance of the participating students in terms of their critical reading skills in favor of the experimental group. Moreover, there was a main effect of gender (in favor of females) on the level of performance of the participating students in terms of their critical reading skills. However, there was no statistically significant interaction between gender and treatment (i.e., teaching method). A number of recommendations were offered in light of the results of the present study